THE USE OF VOCABULARY SELF-COLLECTION (VSS) STRATEGY IN INCREASING STUDENT READING COMPREHENSION - Emeliya Sukma Dara Damanik; Sholihatul Hamidah Daulay; Rora Rizky Wandini; Isnaini Siagian (English Education Department, 2021)
Lack of vocabulary became a problem on student reading comprehension. This condition brings the writers to solve student’s problem by applying of vocabulary self-collection strategy. Several researchers conducted the effect of vocabulary self-collection in teaching language learning. The results showed that this strategy is effective to help students in language learning. Therefore, writers intrigued to apply this strategy. Vocabulary self-collection strategy is an interactive-learning instructional strategy that shows the word consciousness To implement this strategy, the writers used Classroom Action Research. It took four steps proposed by Kemmis and Taggart, Planning, action, observation and reflection. This research took 36 students in Mas Al Ulum Medan. Based on the two cycles, it can be proved that the mean score is higher in the second cycle. The mean score of first cycle was 65,7 %. Furthermore, it was categorized as the criteria of not success in test reading. If we compare to the diagnose test before, it seem the significant differences among of them. Moreover, the use of vocabulary self-collection strategy is not only increase student reading comprehension but also student’s curiosity and interesting in reading of English text. It can be seen from the observation had been done by the researcher and collaborator during the application of this strategy. They looked more active than before. The student enjoyed this strategy because it can help them in reading and memorizing of the word. Therefore, the application of this vocabulary self-collection can be recommended to improve students in reading skill. Furthermore, the result also suggest to teachers, lecturers or other educators to attempt this strategy in supporting of language learning. Because of this strategy is usable to improve student ability in English skill and student’s interest in learning English.